Sleeve Gastrectomy Ameliorates Diabetes-Induced Cardiac Hypertrophy Correlates With the MAPK Signaling Pathway - Xu, Qian; Ding, Huanxin; Li, Songhan; Dong, Shuohui; Li, Linchuan; Shi, Bowen; Zhong, Mingwei; Zhang, Guangyong (Frontiers in Physiology, 2021)
Background: Cardiac hypertrophy as a main pathological manifestation of diabetic cardiomyopathy (DCM), is a significant complication of diabetes. Bariatric surgery has been proven to relieve DCM; however, whether it can alleviate diabetes-induced cardiac hypertrophy is undefined. Methods: Diabetic and obese rats were performed sleeve gastrectomy (SG) after having diabetes for 16weeks. The rats were euthanized 8weeks after SG. Metabolic parameters, heart function parameters, myocardial glucose uptake, morphometric and histological changes, and the expression level of mitogen-activated protein kinases (MAPKs) were determined and compared among the control group (CON group), diabetes mellitus group (DM group), sham operation group (SHAM group), and SG group. Results: Compared with the SHAM group, the blood glucose, body weight, insulin resistance, and other metabolic parameters were significantly improved in the SG group. There was also a marked improvement in myocardial morphometric and histological parameters after SG. Furthermore, the myocardial glucose uptake and heart function were reversed after SG. Additionally, the phosphorylation of MAPKs was inhibited after SG, including p38 MAPKs, c-Jun N-terminal kinases (JNKs), and extracellular signal-regulated kinases 1/2 (ERK1/2). The expression of DUSP6, which dephosphorylates ERK1/2, was upregulated after SG. These findings suggest that SG ameliorated diabetes-induced cardiac hypertrophy correlates with the MAPK signaling pathway. Conclusion: These results showed that diabetes-induced cardiac hypertrophy was ameliorated after SG was closely related to the inhibition of the MAPK signaling pathway and upregulation of DUSP6. Therefore, this study provides a novel strategy for treating diabetes-induced cardiac hypertrophy.